2018
DOI: 10.3390/polym10020201
|View full text |Cite
|
Sign up to set email alerts
|

Renewable, Eugenol—Modified Polystyrene Layer for Liquid Crystal Orientation

Abstract: Abstract:We synthesized a series of plant-based and renewable, eugenol-modified polystyrene (PEUG#) (# = 20, 40, 60, 80, and 100, in which # is the molar content of the eugenol moiety in the side group). Eugenol is extracted from clove oil. We used polymer modification reactions to determine the liquid crystal (LC) orientation properties of the polymer films. In general, the LC cells fabricated using the polymer films with a higher molar content of eugenol side groups exhibited vertical LC orientation behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Therefore, the presence of MCM-41 with eugenol impaired the crystallization of PHBV due to the above-described reduction of the biopolymer segments packing. It has been similarly reported that the addition of mesoporous silica nanoparticles has a slight influence on T g or T m in polymer nanocomposites [60,61], therefore supporting that the here-observed suppressed effect on the melt behavior is ascribed to eugenol. In this sense, Garrido-Miranda et al [62] showed that the T m value of PHB/thermoplastic starch (TPS)/organically modified montmorillonite (OMMT) nanocomposites was reduced by approximately 4 °C when 3 wt.-% eugenol was incorporated, concluding that eugenol induces the formation of less perfect crystals.…”
Section: Resultssupporting
confidence: 78%
“…Therefore, the presence of MCM-41 with eugenol impaired the crystallization of PHBV due to the above-described reduction of the biopolymer segments packing. It has been similarly reported that the addition of mesoporous silica nanoparticles has a slight influence on T g or T m in polymer nanocomposites [60,61], therefore supporting that the here-observed suppressed effect on the melt behavior is ascribed to eugenol. In this sense, Garrido-Miranda et al [62] showed that the T m value of PHB/thermoplastic starch (TPS)/organically modified montmorillonite (OMMT) nanocomposites was reduced by approximately 4 °C when 3 wt.-% eugenol was incorporated, concluding that eugenol induces the formation of less perfect crystals.…”
Section: Resultssupporting
confidence: 78%
“…Referring to improvements in thermoplastics with internal or external plasticization using renewable materials, poly(vinyl chloride) is modified and plasticized by grafting cardanol groups. Polystyrene is also modified with eugenol for liquid crystal orientation [40,41].…”
Section: Contents Of This Issuementioning
confidence: 99%
“…For example, the vertical orientation of LC molecules in LC cells fabricated with PS derivatives substituted with natural extracts such as capsaicin, eugenol, and vanillin, was observed when the substituent ratio was larger than 60 mol%. This is due to the long alkyl groups of the natural extracts, which are related to low surface energy owing to the steric effect of alkyl groups on the polymer film surface [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The surface energy of polymer films and the molecular orientation of the polymers are decisive factors in obtaining vertical LC orientation behavior due to steric repulsion and/or interactions between LC molecules and surfaces [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%